2007
DOI: 10.1007/s11095-007-9370-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural Influence of Isothiocyanates on the Antioxidant Response Element (ARE)-Mediated Heme Oxygenase-1 (HO-1) Expression

Abstract: Collectively, our results demonstrate that the ITC class of compounds activates ARE-mediated HO-1 gene transcription through Nrf2/ARE signaling pathway, however, their inductive effects are quite specific, depending on the chemical structure. These results suggest the possibility that some synthetic ITCs might have superior chemopreventive activity than natural ITCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 22 publications
2
53
2
Order By: Relevance
“…Mechanisms other than the direct modulation of DNA methylation status via inhibition of DNMT and histone deacetylating activities may also be important. Sulforaphane, the active isothiocyanate in cruciferous vegetables, has well documented DNA methylation modifying capabilities, but is also known to activate antioxidant stress response proteins such as hemeoxygenase (HO-1) via antioxidant response element (ARE)-mediated and nuclear factor E2-related factor 2 (Nrf2)-mediated gene transcriptional activation mechanisms [Prawan et al, 2007]. Similarly, lycopene (2-6 lM, 16 hr) has been shown to strongly (2-to 4-fold) induce the expression of reporter constructs containing ARE in MCF-7 and hepatocellular carcinoma HepG2 cells [BenDor et al, 2005]; and lycopene induced (>2-fold) mRNA levels of the endogenous ARE-regulated phase II enzymes, NAD(P)H:quinone oxidoreductase (NQO1) and g-glutamylcysteine synthase (GCS) in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms other than the direct modulation of DNA methylation status via inhibition of DNMT and histone deacetylating activities may also be important. Sulforaphane, the active isothiocyanate in cruciferous vegetables, has well documented DNA methylation modifying capabilities, but is also known to activate antioxidant stress response proteins such as hemeoxygenase (HO-1) via antioxidant response element (ARE)-mediated and nuclear factor E2-related factor 2 (Nrf2)-mediated gene transcriptional activation mechanisms [Prawan et al, 2007]. Similarly, lycopene (2-6 lM, 16 hr) has been shown to strongly (2-to 4-fold) induce the expression of reporter constructs containing ARE in MCF-7 and hepatocellular carcinoma HepG2 cells [BenDor et al, 2005]; and lycopene induced (>2-fold) mRNA levels of the endogenous ARE-regulated phase II enzymes, NAD(P)H:quinone oxidoreductase (NQO1) and g-glutamylcysteine synthase (GCS) in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the same cellular model, Keum et al [19] have confirmed that transcriptional activation of Nrf2/ARE is critical in sulforaphanemediated induction of HO-1. Further evidence of the ability of isothiocyanate to activate ARE-mediated HO-1 gene transcription through Nrf2/ARE signaling pathway has been provided by a study from Prawan et al [20] on HepG2-C8 cells.…”
Section: Isothiocyanatesmentioning
confidence: 98%
“…Thus, similar to many chemically unrelated inducers, administration of isothiocyanate to rodents evoked the 'electrophile counter-attack' response. Molecular studies have shown that isothiocyanates can induce phase 2 enzymes by stimulating transcription of phase II genes via a common antioxidant/ electrophile enhancer element (ARE/EpRE) present in the upstream regions of several phase 2 enzyme genes [39] .…”
Section: Mechanism Of Anticarcinogenic Activitymentioning
confidence: 99%